Sistem Informasi Akuntansi Penjualan dan Penerimaan Pembayaran Piutang Sebagai Alat Keputusan Pemberian Kredit: Studi Kasus pada PT.JSK - Hastoni, Hastoni; Suhendra, Suhendra (Jurnal Ilmiah Ranggagading (JIR), 2007)
As for target is why done/conducted by this research is to measure and know role of sale accounting information system and acceptance of payment of receivable a company conducting activity of sale of yielded goods. Result of research to show that Company have applied accounting information system good enoughly in activity of sale and acceptance of payment of its receivable. Is can be seen from execution of procedure of activity of product selling. For the procedure of giving of credit, the company have determined of giving of policy of credit of its customer/ client type the adapted for the amount of sale as well as its storey;level of him. Information of sales department also assist in determining policy of company credit to customer/ client. Result of evaluation in this research of company the show that in accounting information system there are duplication of function in compared of sale procedure. The mentioned seen from accounting function which double also as credit function so that in is internal of control assessed is unfavourable. Besides in execution of credit to [customer/ client] of company still disregard because reason to take care of potency of customers. For that company require to pay attention the things because with existence of good system development and repair of company can assess customer/ client and give credit as according to customer/ client criterion. Keywords : accounting information system, credit